Exploring the Relationship Between Value-Added Tax Awareness and Consumer Purchasing Decisions in Digos City - Alcantara, Ramlyn Kyzyl; Banay, Richard (12th International Scholars Conference 2025, 2026)
This study examines the level of VAT awareness among consumers in Digos City and how it influences their purchasing decisions in terms of pricing and product information. This study highlights the importance of tax policy awareness and aims to bridge the literacy gap, enabling well-informed consumers to make informed decisions. A quantitative research design was employed, utilizing statistical tools such as ANOVA, regression, and Pearson's correlation. A survey instrument was used to capture the opinions of consumers from diverse demographic groups categorized by Gender, generation, education, and income. Results reveal that consumers in Digos City have a high level of awareness and make high-quality purchasing decisions. It also shows that VAT awareness has a moderate influence on consumer behavior, with significant differences based on education and income levels. Consumers with higher education and income demonstrated greater VAT awareness and more informed purchasing decisions, while Gender and generation showed minimal impact. This research aims to raise awareness of targeted VAT education, as it has been revealed that knowledge of VAT significantly impacts purchasing decisions made every day of our lives. This study advocates for stronger tax literacy, particularly regarding VAT, as consumers ultimately bear the financial burden of a tax legally imposed on sellers.